A qualitative analysis of interprofessional healthcare team members' perceptions of patient barriers to healthcare engagement. Issue 1 (December 2016) - Powell, Rhea; Doty, Amanda; Casten, Robin; Rovner, Barry; Rising, Kristin
Abstract Background Healthcare systems increasingly engage interprofessional healthcare team members such as case managers, social workers, and community health workers to work directly with patients and improve population health. This study elicited perspectives of interprofessional healthcare team members regarding patient barriers to health and suggestions to address these barriers. Methods This is a qualitative study employing focus groups and semi-structured interviews with 39 interprofessional healthcare team members in Philadelphia to elicit perceptions of patients' needs and experiences with the health system, and suggestions for positioning health care systems to better serve patients. Themes were identified using a content analysis approach. Results Three focus groups and 21 interviews were conducted with 26 hospital-based and 13 ambulatory-based participants. Three domains emerged to characterize barriers to care: social determinants, health system factors, and patient trust in the health system. Social determinants included insurance and financial shortcomings, mental health and substance abuse issues, housing and transportation-related limitations, and unpredictability associated with living in poverty. Suggestions for addressing these barriers included increased financial assistance from the health system, and building a workforce to address these determinants directly. Health care system factors included poor care coordination, inadequate communication of hospital discharge instructions, and difficulty navigating complex systems. Suggestions for addressing these barriers included enhanced communication between care sites, patient-centered scheduling, and improved patient education especially in discharge planning. Finally, factors related to patient trust of the health system emerged. Participants reported that patients are often intimidated by the health system, mistrusting of physicians, and fearful of receiving a serious diagnosis or prognosis. A suggestion for mitigating these issues was increased visibility of the health system within communities to foster trust and help providers gain a better understanding of unique community needs. Conclusion This work explored interprofessional healthcare team members' perceptions of patient barriers to healthcare engagement. Participants identified barriers related to social determinants of health, complex system organization, and patient mistrust of the health system. Participants offered concrete suggestions to address these barriers, with suggestions supporting current healthcare reform efforts that aim at addressing social determinants and improving health system coordination and adding new insight into how systems might work to improve patient and community trust.